Evaluation of a Scale for Assessing Medical Students' Attitudes to the Social Dimensions of Health and Preventive Services - Meltem Ciceklioglu; Zeliha Ocek; Safak Taner; Meral Turk; Feride Aksu Tanik; Kivanc Yuksel (Turkish Society of Public Health Specialists, 2012)
Abstract Objective: The purpose of this study was an evaluation of the reliability and validity of a scale for medical students' attitudes towards the social dimensions of health and preventive services.  Method: 255 (72.9%) out of 350 fourth-year and 304 (83.9%) out of 83.9% of 362 sixth-year students in Ege University Medical Faculty participated the study at the beginning of the 2005-2006 academic-year. The reliability and validity of the scale, which was developed by the researchers, were assessed by Cronbach-alpha coefficients  and factor-analysis. Results: Three factors emerged (the importance of preventive services; the importance of the social dimensions of health; responsibilities in  preventive services) from the factor analysis. These factors explained 48.4% of the total variance. Cronbach alpha value was 0.77.  Conclusion: The scale developed and evaluated in this study is a reliable, valid and practicable tool which can be used in the assessment of medical students' attitudes. Key Words: Undergraduate medical education, attitude of medical students, preventive health services, social dimension of health, validity Öğrencilerin Sağlığın Sosyal Boyutu ve Koruyucu Hizmetler ile İlgili Tutumlarını Belirleyen Bir Ölçeğin Değerlendirilmesi Özet Amaç: Bu çalışmanın amacı tıp öğrencilerinin sağlığın sosyal boyutu ve koruyucu hizmetler ile ilgili tutumlarını belirlemeye yönelik bir ölçeğin güvenilirlik ve geçerliliğinin belirlenmesidir. Yöntem: Çalışmaya 2005-2006 öğrenim yılının başında  dördüncü sınıfta olan 350 öğrencinin 255'i (% 72.9) ve altıncı sınıf olan 362 öğrencinin 304'ü (% 83.9) katılmıştır. Araştırıcılar tarafından geliştirilmiş olan ölçeğin güvenilirlik ve geçerliliği Cronbach-alpha değeri ve faktör analizi aracılığı ile değerlendirilmiştir. Bulgular: Faktör analizi sonucunda üç tema belirlenmiştir (koruyucu hizmetlerin önemi, sağlığın sosyal boyutunun önemi, koruyucu hizmetlerde sorumluluklar). Faktörler toplam varyansın % 48.4'ünü açıklamış, Cronbach-alpha değeri 0.77 olarak bulunmuştur. Sonuç: Bu çalışmada geliştirilen ve değerlendirilen ölçek tıp öğrencilerinin tutumlarının ölçülmesi amacıyla kullanılabilecek, güvenilir, geçerli ve pratik bir araçtır. Anahtar Kelimeler: Mezuniyet öncesi tıp eğitimi, tıp öğrencilerinin tutumları, koruyucu sağlık hizmetleri, sağlığın sosyal boyutu, geçerlilik